Male image, female gaze : men in Shashi Deshpande's fiction - Singh, Manpreet J. (Rawat Publications, 2012)
The novels of Shashi Deshpande have frequently been analyzed through the traditional feminist framework, an attempt sometimes contested by the writer, although she writes unambiguously from the female point of view. Male Image, Female Gaze analyzes Deshpande's apparently dichotomous stance and elaborates on her departure from the limited scope of theoretical assumptions. The book focuses on Deshpande's understanding of contextual peculiarities and the need to affect sustainable shifts from within social and relational structures. Instead of viewing men as antagonists, she therefore considers the possibility of men as a medium for an integrated and inclusive change. The intricate working of the resistant male psyche is observed and tackled, not from a belligerent but an analytical point of view. Deshpande's purpose is to locate constraints on masculine identity which hamper the reshaping of the gender paradigm, and to consider factors which could impel men to move out of them. Male Image, Female Gaze also examines Deshpande's portrayal of husbands, brothers, sons, and fathers to throw light on the slow pace of social change, as it works its way through underlying psychological conflicts and crises of identities. The book brings into focus her assessment of the inbuilt flexibility of human nature which eventually adapts to changing situations, creating openings where none existed.